Peran Teman Sebaya Dalam Mengembangkan Kecerdasan Sosial Peserta Didik (Studi Deskriptif Kualitatif di Kelas VII D SMP Negeri 29 Bandung) - Astuti, Fuji; Sapriya, Sapriya; Jupri, Jupri (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study focuses on four aspects of social intelligence, namely communication, respecting differences of opinion, problem solving and empathy based on Goleman's theory. All four are related to social studies learning which trains students to be able to communicate, appreciate, interact and socialize with the community. This research was conducted because there is still a lack of respect for differences of opinion in students and a lack of ability to build closeness with peers other than close friends. The purpose of this research was to find out the role of peers in developing students' social intelligence. In order to achieve this goal, this research was conducted using a qualitative approach and descriptive method, so the data collected came from research results by conducting observations, interviews, and documentation. The results of this study indicate that the role of peers is to provide assistance in developing communication skills so that students are able to build social relationships, students are able to appreciate differences of opinion so that they are able to accept criticism and suggestions, an increase in problem solving skills is seen when students help each other in doing a difficult task, the attitude of empathy that students have increases is reflected in students having sensitivity to the feelings of others. In addition, there is a link between social intelligence and social studies learning objectives, namely to equip students to become good and responsible citizens so that students have the provisions to enter social life.